Comparative transcriptome profiling reveals distinct regulatory responses of secondary defensive metabolism in Datura species (Solanaceae) under plant development and herbivory‐mediated stress - Eunice Kariñho Betancourt; Nancy Calderón Cortés; Rosalinda Tapia López; Ivan De‐la‐Cruz; Juan Núñez Farfán; Ken Oyama (Ecology and Evolution, 2024)
Abstract Differential expression of genes is key to mediating developmental and stress‐related plant responses. Here, we addressed the regulation of plant metabolic responses to biotic stress and the developmental variation of defense‐related genes in four species of the genus Datura with variable patterns of metabolite accumulation and development. We combine transcriptome profiling with phylogenomic techniques to analyze gene expression and coexpression in plants subjected to damage by a specialist folivore insect. We found (1) common overall gene expression in species of similar chemical profiles, (2) species‐specific responses of proteins involved in specialized metabolism, characterized by constant levels of gene expression coupled with transcriptional rearrangement, and (3) induction of transcriptional rearrangement of major terpene and tropane alkaloid genes upon herbivory. Our results indicate differential modulation of terpene and tropane metabolism linked to jasmonate signaling and specific transcription factors to regulate developmental variation and stress programs, and suggest plastic adaptive responses to cope with herbivory. The transcriptional profiles of specialized metabolism shown here reveal complex genetic control of plant metabolism and contribute to understanding the molecular basis of adaptations and the physiological variation of significant ecological traits.